Camping it out in the Never Never: Subverting Hegemonic Masculinity in The Adventures of Priscilla, Queen of the Desert (Stephan Elliott, 1994) - Anne Le Guellec-Minel (Revue LISA)
The critical and popular success of Priscilla, Queen of the Desert (Stephan Elliott, 1994) helped to put the Australian film industry on the world map and made Stephan Elliott’s feature a cult film in its own right. The article explores how the aesthetics and politics of kitsch, which allow the film to balance subversion and conservatism, may have been the recipe for success. Priscilla belongs to the Australian subgenre of the “Glitter cycle” which charts the rise of ordinary nobodies to fame, affirming aesthetic tackiness against elitist good taste. Yet the film takes the consensual optimism of the glitter comedy further back to the societal and geographical margins of Australia. Leaving behind the urban gay scene, the film subversively relocates two icons of queer culture, the drag queen and the transsexual, in the sublime landscapes of the Outback that have helped forge the Australian myth of heroic masculinity. Although this queering of the myth does not do away with the hostile stereotypes traditionally projected on women and other marginalized groups, it does bring out the camp quality of the Australian sublime.